O conceito de coletividade de Anton Makarenko, em seu Poema pedagógico - Bretas, Silvana Aparecida [UNESP]; Novaes, Karla Gusmão (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2016)
The article is a bibliographical research that analyzes the Pedagogical Poem (1935), by Anton Makarenko, in order to approach the concept of collectivity inscribed in the educational experience of Gorky Colony, located in the distant and frozen territory of the once Union of Soviet Socialist Republics (USSR). The Pedagogical poem is a narrative that describes Makarenko's practices regarding the education of young offenders in the colony after the Socialist Revolution. For this educator, the collective is built around daily interaction between learners and educators.

Trata-se de pesquisa bibliográfica que analisa o texto Poema pedagógico (1935), de Anton Makarenko, a fim de abordar o conceito de coletividade inscrito na experiência educacional da Colônia de Gorki, situada no longínquo e congelado território da então União das Repúblicas Socialistas Soviéticas (URSS). Makarenko, em seu texto narrativo, descreve vivências de suas práticas, após a Revolução Socialista, na colônia destinada à educação de jovens infratores. Para o educador, o coletivo se constrói na convivência diária entre educandos e educadores.
Anton Makarenko's concept of collectivity in his Pedagogical poem
Keywords: collectivity; socialist education; training process; pedagogical experience; organic intellectual; coletividade; educação socialista; processo de formação; experiência pedagógica; intelectual orgânico